Manajemen Risiko Teknologi Informasi Pada BTSI UKSW Menggunakan ISO 31000:2018 - Vincent Patrick Pratama Wijaya (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
Biro Teknologi dan Sistem Informasi (BTSI) is one of the service units tasked with developing and supporting the needs of the academic community regarding the needs of information technology. BTSI always maintains system security and carries out regular maintenance for the smooth running of service and development activities at BTSI. Research conducted at the Bureau of Technology and Information Systems regarding the analysis of risk management using the ISO 31000:2018 framework was compiled with several stages starting from the stages of identification, analysis, evaluation, to risk treatment. In order to achieve this goal, a governance risk management is needed so that BTSI can mitigate incidents that will occur in the future. However, threats and risks that may occur later are things that must be anticipated and are very likely to occur. The disruption of business processes until the cessation of all activities at BTSI is the impact of possible threats that will occur, but BTSI can face previous risks and re-launch existing business processes. Therefore, it is important to understand the risks that can affect BTSI's business processes.